Beton Bermutu Dan Ramah Lingkungan Dengan Memanfaatkan Limbah Abu Ban Bekas - Simanjuntak, Johan Oberlyn; Saragi, Tiurma Elita; Sidabutar, Ros Anita; Pasaribu, Humisar; Simbolon, Rido Parulian (Jurnal Visi Eksakta, 2021)
The need for housing is increasing day by day. This is a factor in the visit to the need for concrete as a housing construction material. The more concrete that is produced, the more cement is needed for the construction. Concrete is a composite material (mixture) of several materials, the main ingredient of which consists of a mixture of cement, fine aggregate, coarse aggregate and water. Utilization of waste tire ash in the concrete mix is one of the alternative uses so that ic can ultimately increase the efficiency of cement savings which takes a long time to increase in high prices. With reference to this, this study uses used waste as a cement additive with a mixture composition of 0%, 3%, 6% and 9%. The test specimens were made using a cylinder with a diameter of 15 cm and a height of 40 cm with 48 specimens produced. The results of the compressive strength test of normal concrete (25.45 MPa), while the concrete with a mixture of 3% used tire ash (28.15 MPa), 6% used tire ash mixture (23.46 MPa) and 9% used tire ash mixture (18.60 MPa). From this research, it can be said that compressive strength of concrete using 3% ash produces the greatest compressive strength of 28.15 MPa.